O papel da equipe de enfermagem obstétrica na gestão ao parto normal. - Arnaldo Ferreira Pereira; Andreza Barbosa Silva Cavalcanti (Revista ft, 2026)
The role of the obstetric nursing team in the management of normal labor integrates a care model focused on promoting female autonomy and reducing unnecessary interventions in the birth process. This study analyzes the performance of obstetric nurses in assisting physiological labor, identifying their care practices, the regulatory norm framework, and the main institutional barriers experienced in the hospital environment. This is an integrative literature review with a qualitative and descriptive approach, guided by the PICo strategy and developed through consultations of SciELO, BDENF, and LILACS databases, in addition to documents from the Ministry of Health, Federal Nursing Council, and World Health Organization, totaling 15 sources submitted to thematic-categorical analysis. The results indicate that the obstetric nurse employs non-invasive care technologies, such as ambulation, massages, and non-pharmacological methods of pain relief, redefining the woman's role as the central protagonist. Solid legal support is demonstrated by Decree No. 94.406/87, COFEN Resolution No. 0477/2015, and Law No. 11.108/2005. However, institutional barriers persist, represented by work overload, deficient physical infrastructure, and resistance from teams under the interventionist biomedical model. It is concluded that the management of normal labor by obstetric nursing consolidates humanized and safe care, requiring continuous investments in hospital infrastructure and multiprofessional training.